Atypical manifestations of COVID-19 in general practice: a case of gastrointestinal symptoms. Issue 8 (27th August 2020) - Wahab, Sardam Faraidon; Løgstrup, Brian Bridal
Abstract : During the previous months, we have seen the rapid pandemic spread of SARS-CoV-2. Despite being considered a respiratory virus, it has become clear that other clinical presentations are possible and some of these are quite frequent. In this paper, a case of a man in his late 70s showing atypical symptoms in general practice is presented. Apart from fever, the patient complained of diarrhoea, borborygmus, loss of appetite and nausea. He developed no respiratory symptoms during his disease. Due to his symptoms, malignant disease was suspected, and he was referred for further testing which revealed typical COVID-19 findings on a chest CT scan. The occurrence of atypical symptoms is discussed, including the importance of recognising these in an ongoing pandemic.